Pemetaan Kebisingan Menggunakan Software Golden Surfer 16 di PT. Terminal Teluk Lamong - Praditya Sigit Ardisty Sitogasa; Sophia Alvin Nurina Yulia Masladen (Prosiding ESEC, 2023)
PT. Teluk Lamong Terminal (TTL) is an international multi-purpose logistics terminal owned by PT Pelabuhan Indonesia (Persero) which serves activities such as shipping and receiving containers and dry bulk. TTL impacts the surrounding environment, especially noise. High noise level around PT. Teluk Lamong Terminal has the potential to cause dangerous impacts on workers and the surrounding environment. Thus, research was conducted to evaluate noise levels and noise distribution patterns from seven points around PT. Teluk Lamong Terminal, using Surfer 16 and Google Earth software. The noise measurement location was determined using the sampling point method in accordance with the SNI 8642:2017 standard method. The measurement values are then compared to the noise level standards stipulated in the Decree of the State Minister for the Environment Number 48 of 1996. The measurement results show that the noise level at PT. Teluk Lamong Terminal exceeds the specified threshold value. The entrance to Teluk Lamong Terminal has a noise level of 75 dBA, exceeding the threshold value of 70 dB, while the Tambak Langon Aserowo settlement has a noise level of 56 dBA, exceeding the threshold value of 55 dB. Noise mapping shows that the main source of noise comes from fluctuations in the volume of vehicles passing through these areas, especially at certain times when traffic is denser.